Comprehensive characterization of a transgene insertion in a highly repetitive, centromeric region of Anopheles mosquitoes. (3rd April 2023) - Vitale, Matteo; Leo, Chiara; Courty, Thomas; Kranjc, Nace; Connolly, John B.; Morselli, Giulia; Bamikole, Christopher; Haghighat-Khah, Roya Elaine; Bernardini, Federica; Fuchs, Silke
ABSTRACT: The availability of the genomic sequence of the malaria mosquito Anopheles gambiae has in recent years sparked the development of transgenic technologies with the potential to be used as novel vector control tools. These technologies rely on genome editing that confer traits able to affect vectorial capacity. This can be achieved by either reducing the mosquito population or by making mosquitoes refractory to the parasite infection. For any genetically modified organism that is regarded for release, molecular characterization of the transgene and flanking sites are essential for their safety assessment and post-release monitoring. Despite great advancements, Whole-Genome Sequencing data are still subject to limitations due to the presence of repetitive and unannotated DNA sequences. Faced with this challenge, we describe a number of techniques that were used to identify the genomic location of a transgene in the male bias mosquito strain Ag(PMB)1 considered for potential field application. While the initial inverse PCR identified the most likely insertion site on Chromosome 3 R 36D, reassessment of the data showed a high repetitiveness in those sequences and multiple genomic locations as potential insertion sites of the transgene. Here we used a combination of DNA sequencing analysis and in-situ hybridization to clearly identify the integration of the transgene in a poorly annotated centromeric region of Chromosome 2 R 19D. This study emphasizes the need for accuracy in sequencing data for the genome of organisms of medical importance such as Anopheles mosquitoes and other tools available that can support genomic locations of transgenes.